Pengaruh Teman Sebaya Terhadap Gaya Hidup Hedonisme Siswa di SMP Negeri 1 Lembah Melintang - A, Angreni (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Hedonistic lifestyle is a social disease that prioritizes excessive financial pleasure, seen from the pattern of thinking and instant lifestyle. In the Al-Qur'an Surah Al-Hadid verse 20, Allah SWT explains that Hedonism is capable of bringing disgrace and loss, but currently the Hedonistic lifestyle is increasingly developing, as research is motivated by the phenomenon found in students at SMP Negeri 1 Lembah Melintang, which is indicated. Some students don't get enough support from peers, don't use their time, join in, everything is instant and have a materialist and consumerist attitude. The aim of the research is to find out how much influence peers have on the Hedonism lifestyle. The research method used is descriptive quantitative research, data collection through questionnaires and sampling techniques using Stratified Random Sampling using the Slovin formula. The results of the research based on simple linear regression analysis obtained a value of Sig 0.04 <0.05, meaning that peers influence the hedonistic lifestyle. Based on the T test, the results obtained were tcount 2.050 > ttable 1.98896 so it can be concluded that Ha is accepted, meaning there is peer influence. towards a hedonistic lifestyle and an R square value of 54.8%, it is stated that peers have quite a big influence in determining lifestyle, and the rest is influenced by other factors. It is hoped that this research can serve as a guide for counselors in developing guidance and counseling approaches and services related to peers and hedonistic lifestyles.